Safety Citizenship Behaviors (SCBs) BUMDesa Managers through Tourism Management in Sumenep Regency - Faidal Faidal; Bambang Setiyo Pambudi (Unversitas Muhammadiyah Mataram, 2024)
Abstract: Risk management is an integral part of a business because it has a high environmental, human, legal, and financial impact, including the tourism business. Today's organizations focus on building human risk management systems, limiting risky behaviour, and improving safety behaviour. Based on previous research, compliance with safety rules and regulations significantly minimizes the risk of work accidents. However, safety researchers recognize that compliance alone is not enough to achieve high levels of safety. Organizations need individuals who are also proactive in participating and initiating safety improvements. This type of proactive behaviour is called safety citizenship behaviour. The present study addressed this issue by examining the dimensionality of SCBs as they relate to helping, stewardship, civic virtue, whistleblowing, voice, and initiating change in current practices. Data on SCBs were collected from four districts in Madura. This study was carried out with the following: (1) Calculate descriptive statistics (2) normality test; (3) The use of the structural equation model (SEM) to test concurrent models in the different samples using confirmatory factor analyses (CFA); and (4) multi-group invariance testing.